Period poverty among women after the 2023 Kahramanmaras Earthquake in Turkey-a cross-sectional study - Dal, Nursel Alp; Kurt, Nuray; Beydag, Kerime Derya; Aruser, Ulkin Gunduz; Nagorska, Anna; Nagorska, Malgorzata (Inst Rural Health Lublin, Poland, 2025)
Introduction and objective: Menstrual poverty lies at the intersection of poverty, sustainability, reproductive rights, and gender inequality. The study investigates menstrual poverty among women affected by the 2023 earthquake in Turkey. Material and methods: A descriptive cross-sectional study was conducted between 24 April - 24 May 2023 with 400 women impacted by the earthquake. Data were collected via social media using a survey form. Chi-square tests, Bonferroni test, and binary logistic regression model were used for statistical analysis. Results: The mean age of participants was 27.27 +/- 8.40 years; 69.5% had higher education, 57.0% lived in urban areas, and 90.5% had no chronic disease. A significant relationship was found between access to menstrual products and basic needs (clean water, toilet paper, soap, safe toilet access, and healthcare) during menstruation after the earthquake (p<0.05). A significant correlation was also observed between disruptions to the menstrual cycle and the following variables: lack of privacy, perception that lack of privacy affected menstruation, healthcare access, and difficulty obtaining menstrual products (p<0.05). Conclusions: Most participants faced difficulties accessing menstrual products, water, hygiene supplies, privacy, and healthcare. Those living in tents or containers reported greater challenges. These barriers contributed to menstrual poverty and impacted women's cycles. As menstrual health and hygiene are basic needs and human rights, menstrual poverty must be addressed globally
Keywords: period poverty; menstruation; women; hygiene; earthquake